Coverage and Power in Genomewide Association Studies - Jorgenson, Eric (The American Society of Human Genetics, 2006)
The ability of genomewide association studies to decipher genetic traits is driven in part by how well the measured single-nucleotide polymorphisms “cover” the unmeasured causal variants. Estimates of coverage based on standard linkage-disequilibrium measures, such as the average maximum squared correlation coefficient (r(2)), can lead to inaccurate and inflated estimates of the power of genomewide association studies. In contrast, use of the “cumulative r(2) adjusted power” measure presented here gives more-accurate estimates of power for genomewide association studies.